ANALISIS SWOT PENERAPAN BUDAYA LITERASI SISWA SMA DI SMAN 1 MUNTILAN - Fadma Rosita; M Rudi Gunawan Parozak (Jurnal Ilmiah Global Education, 2023)
The purpose of this study is to analyze the strategy for implementing literacy culture using the SWOT analysis model, then draw conclusions and decide on policies to be implemented.This research method is a descriptive case study method. This research was conducted at SMA N I Muntilan, Yogyakarta. The research was conducted in March 2021. The data sources from this research were participants, informants, informants, and teachers. Data collection techniques in descriptive case study research are documents, archival records, interviews, direct observation, participant observation, and physical devices. The data analysis technique used in analyzing the problem formulation is an interactive technique. The results of the research that has been done are as follows: 1) the strategies applied in managing literacy culture are very good. Managed by teachers and librarians who are ready to guide students in implementing literacy programs. 2) the results of the SWOT analysis show that the school has sufficient strength in supporting facilities and infrastructure. High student interest in digital literacy. 3) the weakness in implementing an iteration culture is the lack of qualified human resources who are serious about managing the implementation of a literacy culture in schools. What needs to be improved is the addition of human resources that are directly related to digital literacy. Training for student representatives in increasing digital literacy is also urgently needed.